The Effectiveness of the Principal's Working Group of Public Elementary Schools in Indonesia - Khodijah, Siti; Widayatsih, Tri; Fitriani, Yessi (Journal of Social Work and Science Education, 2021)
This study is to determine the actions of the Principal Working Group of SD Negeri in Lumpatan Village, Musi Banyuasin Regency related to planning, organization, implementation, and supervision. The descriptive qualitative approach was used in this study. Techniques for gathering data include observation, interviews, and documentation. The findings indicate that on the planning dimension, the indicators that are less effective are human resources who do not yet have good managerial performance and competence in supporting the preparation of work plans, on the organizational dimension, the indicators for preparing the Principal Working Groups plan and education and training indicators are not running effectively, on the dimension of implementation, what is to be achieved is not running effectively.